Environmental Cost, Intellectual Capital and Company Size as Predictor of Companies Financial Performance - Fitria Arzaqina; Mustanwir Zuhri; Rizki Yuniarti; Riza Zahrotun Nisa (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2026)
Abstract – This study aims to determine the effect of environmental cost, intellectual capital, and company size on financial performance as measured by return on assets (ROA). The important role of the palm oil industry in Indonesia, issues concerning the sustainability of this industry, and the instability of average ROA over the past five years form the background for this study. The research data used a purposive sampling method to obtain 11 palm oil plantation companies listed on the Indonesia Stock Exchange (IDX) for the period of 5 years from 2019 to 2023. The analytical technique used in this study is panel data regression with a common effect model approach. This study used the Econometric Views (Eviews) version 12 software as the analytical tool. The results of this study indicate that environmental cost has no effect on ROA, intellectual capital has a positive effect on ROA, and company size has no effect on ROA. Simultaneously, environmental cost, intellectual capital, and company size affect ROA. Keywords: environmental cost, intellectual capital, company size, financial performance